Differences in Thigh Muscle Activation Between Standing and Landing Exercises for Knee Injury Prevention and Rehabilitation - Jesper Bencke; Mark Strøm; Derek J. Curtis; Thomas Bandholm; Mette K. Zebis (North American Sports Medicine Institute, 2023)
# Background In injury prevention or rehabilitation programs, exercises that facilitate enhanced hamstring activity may be beneficial when aiming to enhance knee joint stability during movements in sports with higher risk of acute knee injury. Information about neuromuscular activation of the hamstring muscles in commonly used exercises may improve exercise selection and progression in programs for knee injury prevention or rehabilitation. # Purpose To investigate (1) how balance devices with progressing degrees of instability influence the activity of muscles controlling the knee joint in typical balance exercises with different demands on postural control, and (2) if any between-sex differences exist. # Study design Cross-sectional study. # Methods Twenty habitually active healthy adults (11 males) participated in this cross-sectional study. Single-leg stance, single-leg squat and single-leg landing were performed on the floor and two different balance devices imposing various levels of challenge to postural control. Three-dimensional motion analysis was used to obtain hip and knee joint angles, and as primary outcomes, and peak normalized EMG activity from the hamstrings and quadriceps muscles was measured for comparison between exercises. # Results The more challenging in terms of maintaining stable balance the devices were, the higher hamstring muscle activity levels were observed. There was a clear progression across balance devices from single-leg stance to single-leg squat and further to single-leg landing displaying increasing hamstring activity levels. The change in medial hamstring activity across all devices when changing from single-leg squat to single-leg landing was significantly higher for the female participants than for the males reaching a higher level of activity. # Conclusion The muscle activity of the hamstrings and quadriceps increased when the motor task was more dynamic. Specifically, single-leg landings were effective in increasing the hamstring muscle activity over the single-leg stance to single-leg squat exercises, and muscle activity was significantly increased with the most unstable device. Increases in hamstring muscle activation was greater in female subjects than males with increasing instability of the balance devices. # Trial identifier Not registered. # Level of evidence 3